Teaching Resilience to People With Visual Disabilities - Rosado, Inger Solange Maitta; Ortega, Jenmer Maricela Pinargote; Medranda, Eva Alcivar; Basurto, Elisa Ximena Coello (International Research Journal of Management, IT & Social Sciences, 2018)
The objective of the research is to develop resilience in people with visual disabilities at the Technical University of ManabÃ. The work offers a conceptual analysis on visual disability in students. It deals with what is related to the conceptual understanding of resilience, where several authors who have studied the subject are analyzed. The resilient capacity of students with visual impairment and the importance of psychological support is analyzed. The importance of the intervention in resilience is exposed, where the content of the Manual of Intervention in Resilience of Eugenio Saavedra 2011 is analyzed. The results of the measurement of resilience are shown in the students of the Technical University of ManabÃ who suffer from a visual disability and the situation that could be verified after applying the work of training in resilience to said personnel. Finally, the conclusions of the work are exposed, where the relevance of the study is demonstrated and a group of recommendations is made based on the importance of the results obtained in the research.